Access to 1H-indazoles, 1H-benzoindazoles and 1H-azaindazoles from (het)aryl azides: a one-pot Staudinger-aza-Wittig reaction leading to N–N bond formation?. Issue 60 (12th July 2018) - Alaime, T.; Daniel, M.; Hiebel, M.-A.; Pasquinet, E.; Suzenet, F.; Guillaumet, G.
Abstract : One-pot synthesis of 1 H -indazole derivatives through a proposed Staudinger-aza-Wittig tandem mechanism Abstract : The synthesis of various substituted 1 H -indazoles is reported through N–N bond formation from an iminophosphorane derivative. Supported by control experiments, an original Staudinger-aza-Wittig tandem mechanism is proposed for this transformation.